Analysis Of Sources And Use Of Working Capital At North Sumatra Bank For The 2019-2020 Period - Supardi Supardi; Imamah Khairiyah; Fitriani Fitriani (Politeknik Siber Cerdika Internasional, 2022)
The purpose of this study was to analyze and find out the results of the analysis of sources and use of working capital at Bank Sumut for the 2019-2020 period. This research uses descriptive analysis. The object of this research is the Bank of North Sumatra. The type of data used in this study is quantitative data in the form of company financial records at Bank Sumut in 2019-2020. Sources of data used in this study using secondary data sources. The results showed that there was an increase in working capital seen from the table of changes in working capital and the table of sources of working capital use at Bank Sumut, as well as an increase in working capital with quantitative concepts, qualitative concepts and functional concepts in 2019 to 2020.